Green Innovation and Energy Efficiency: Moderating Effect of Institutional Quality Based on the Threshold Model - Chen, Chaoyi; Pinar, Mehmet; Roman-Collado, Rocio (Environmental and Resource Economics, 2024)
Recent studies demonstrated that green innovation and environment-related technologies reduce energy intensity and improve energy efficiency, contributing to the reduction of carbon emissions. However, the existing studies employ linear estimation methods
Keywords: Energy Efficiency; Green Innovation; Institutional Quality; Threshold Model; Energy Intensity